Outcome study of the pipeline embolization device for treatment of intracranial aneurysms at a single UK institution. (2nd November 2017) - Yang, Shih-Hung; Hampton, Timothy; Kandasamy, Naga; Hart, Jonathan; Ashmore, Jonathan; Walsh, Daniel C.; Tolias, Christos M.; Booth, Thomas C.
Abstract: Background: The introduction of flow-diverting stents in the last decade provides an alternative endovascular treatment choice in selected intracranial aneurysms. This retrospective analysis of a UK centre's experience provides insight into clinical and radiographic outcomes. Methods: Electronic patient records, diagnostic and procedural images and written procedural records for patients treated with the PED between August 2009 and April 2014 were reviewed. Follow-up TOF MRA was performed after treatment. Clinical and radiographic outcomes were analyzed and compared with other PED studies. Results: Twenty-nine patients with 30 attempted PED treatments were reviewed representing 3.5% of the treated aneurysm patient cohort. 63.6% (21/33) of the aneurysms were wide-necked (>4 mm), 60.6% (20/33) were large or giant (≥10 mm). The mean aneurysm sac diameter was 12.0 mm; the mean neck width was 4.5 mm. Mortality and morbidity rates were 3.3% and 10.0%, respectively. The total adequate occlusion rate was 78.1% (25/32) at 18 months. The neck width of aneurysms with residual sac filling and complete occlusion differed significantly ( p = 0.04). Conclusions: Highly selected aneurysms treated with a PED in a UK centre have similar occlusion and complication rates when compared to non-UK studies. Again, it appeared that delayed aneurysm rupture remained a risk for PED treatment in large or giant aneurysms. Follow-up with TOF MRA gave similar occlusion results compared to those obtained with DSA in other studies. The influence of neck size on occlusion rate should be examined in future PED studies.